Correction: Cost-effectiveness of pulse oximetry and integrated management of childhood illness for diagnosing severe pneumonia. - PLOS GLOBAL PUBLIC HEALTH Staff (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0000757.].